Analisis Efisiensi Dan Efektifitas Pajak Bumi dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) dan Pengaruhnya terhadap Pendapatan Asli Daerah di Kabupaten Batang Hari - Neng Setiawati; Satya Wahyudi; Novi Aulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the level of efficiency, effectiveness and influence of the Rural and Urban Land and Building Tax (PBB-P2) on Regional Original Income (PAD) in Batang Hari Regency. The data used in this study are primary data obtained from the Regional Finance Agency of Batang Hari Regency and secondary data by conducting library research obtained from the literature and other information related to the problem under study. The analytical tools used are descriptive analysis, growth analysis, contribution/share, efficiency and effectiveness analysis, and simple regression analysis using IBM (Statistical Package for Social Science) SPSS version 26. The results showed that the average level of efficiency of Rural and Urban Land and Building Tax collection (PBB-P2) of 82.98 percent was categorized as quite efficient. The average level of effectiveness of PBB-P2 is 56.87 percent, including the less effective category. The results of the regression calculations show that the PBB-P2 variable has no effect on PAD receipts in Batang Hari Regency.